A systematic review of the literature on integrating sustainability into engineering curricula. (20th April 2018) - Thürer, Matthias; Tomašević, Ivan; Stevenson, Mark; Qu, Ting; Huisingh, Don
Abstract: Higher education plays an important role in furthering the sustainability agenda, as reflected in a growing body of literature. While there have been several recent reviews of this work, these have been limited in scope and do not explicitly discuss implementations of sustainability in higher education curricula. In response, this paper presents a comprehensive, systematic review of the literature on integrating sustainability into curricula at both an undergraduate and postgraduate level of study in one particular subject area – engineering. A total of 247 articles, of which 70 were case reports, have been analyzed. Twelve future research questions emerged from the analysis, including: the exploration of the knowledge and value frameworks of students and teachers; the exploration of stakeholder influence, including by accreditation institutions, industry partners, parents, and society; and, the use of competencies to evaluate implementations. It is hoped that answering these questions will help to enhance education such that engineers are prepared, engaged, and empowered to confront the environmental, social, and economic challenges of the 21st century. Highlights: Presents a systematic literature review on sustainability in engineering curricula. Provides an important reference guide for the research community. Outlines twelve future research areas to further develop the field.